2016
DOI: 10.1109/tla.2016.7459584
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an Average Tracking Controller that Considers all the Subsystems Involved in a WMR: Implementation via PWM or Sigma-Delta Modulation

Abstract: This paper has two aims; the first, to present the design of a three-level average controller (that do not require electromechanical sensors) for the trajectory tracking task in a differential drive wheeled mobile robot (WMR). Such a controller considers, for the first time in literature, the dynamics of the three subsystems composing a WMR, i.e., mechanical structure, actuators, and power stage. The proposed controller is designed as follows: At the high level, a kinematic control for the mechanical structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…After carrying out the review of the literature associated with design of controllers for the trajectory tracking task in differential drive WMRs, it was found that, generally, this task has been solved in three directions: (a) by only using the kinematic or dynamic model of the mechanical structure , (b) by employing the kinematic/dynamic model of the mechanical structure along with the dynamics of the actuators [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103], and (c) by considering the kinematic model of the mechanical structure along with the dynamics of the actuators and power stage [104,105]. In the last direction, contributions that have carried out interesting efforts are [106][107][108][109][110][111][112][113][114].…”
Section: Discussion and Contributionmentioning
confidence: 99%
See 3 more Smart Citations
“…After carrying out the review of the literature associated with design of controllers for the trajectory tracking task in differential drive WMRs, it was found that, generally, this task has been solved in three directions: (a) by only using the kinematic or dynamic model of the mechanical structure , (b) by employing the kinematic/dynamic model of the mechanical structure along with the dynamics of the actuators [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103], and (c) by considering the kinematic model of the mechanical structure along with the dynamics of the actuators and power stage [104,105]. In the last direction, contributions that have carried out interesting efforts are [106][107][108][109][110][111][112][113][114].…”
Section: Discussion and Contributionmentioning
confidence: 99%
“…Motivated by the aforementioned ideas, the hierarchical control approach in mobile robotics (see [86,104,105,115]), and use of DC/DC converter-DC motor systems (see [116,117]), the purpose of the present paper is threefold. First, it aims, to introduce a three-level hierarchical controller that considers dynamics of the three subsystems that compose a WMR to solve, in a more complete way, the trajectory tracking task.…”
Section: Discussion and Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to literature, several applications have benefited using DC/DC power electronic converters as drivers for DC motors [1][2][3][4][5][6][7]. Particularly, mechanical systems [1], robots [2][3][4], electric vehicles [5], and renewable energy [6,7]. Thereby, the design of controls for DC motors driven by DC/DC power converters is a current research topic.…”
Section: Introductionmentioning
confidence: 99%